INTEGRASI PARAMETER ESG DALAM SISTEM PENILAIAN KELAYAKAN PENJAMINAN KREDIT UMKM: PENDEKATAN RISK-BASED GUARANTEE ANALYSIS - Serang, Adrian Eka Darma (ITB AAS Indonesia Surakarta, 2025)
Access to credit remains one of the most persistent challenges for Indonesian MSMEs, particularly for enterprises that operate without formal collateral or structured financial records. Although MSMEs contribute significantly to national economic resilience, conventional credit assessment procedures often fail to capture the day-to-day realities of their operations. This gap creates a misalignment between the actual risk profile of MSMEs and the decisions made by lenders or guarantee institutions. As the financial sector shifts toward sustainability-oriented practices, the need for a more holistic and behaviour-sensitive guarantee assessment model has become increasingly evident. This study develops and evaluates a risk-based guarantee model that incorporates environmental, social, governance, and business-character indicators as complementary dimensions of MSME risk profiling. A total of 33 indicators were constructed and organized into four weighting categories to reflect their relative contribution to sustainability-related risk. A mixed-method approach was employed. The qualitative stage involved indicator formulation and refinement, while the quantitative stage used confirmatory factor analysis, logistic regression, and predictive performance evaluation through ROC curves, AUC values, and confusion matrices. The results demonstrate that all ESG dimensions meaningfully influence guarantee eligibility. Governance indicators emerged as the strongest predictors, followed by environmental, social, and business-character factors. The model’s classification performance shows notable improvements compared with collateral-based assessments, with higher predictive accuracy and significantly lower misclassification rates. The inclusion of digital transaction data and other alternative data further enhanced the model’s ability to identify behavioural patterns and operational consistency among MSMEs. Overall, the findings indicate that an ESG-integrated guarantee assessment framework offers a practical and adaptive alternative for institutions such as Jamkrindo. The model not only strengthens risk evaluation and reduces claim exposure but also supports broader national objectives in sustainable finance. These insights provide a foundation for developing a more inclusive, data-driven, and sustainability-aligned guarantee ecosystem.